European integration and the case for compensatory regional policy - Christiane Krieger-Boden (Kiel Institute for World Economics (IfW), 2002)
The ongoing process of European integration is likely to increase trade and factor mobility thereby increasing interregional competition and affecting the interregional division of labor. From a theoretical standpoint, rising specialization and polarization of European regions may result from this process, and may entail a growing core-periphery-divide of regional income. Such a supposition evokes questions on the need of an accompanying compensatory regional policy and its adequate design. I find that a case for regional policy cannot be denied, but that the EU largely overstates the need for such a policy at EU level, and should abstain from direct structural interventions into regional economies.
Keywords: F12; F15; N11; R12; R58; 330; regional policy; regional specialization; regional polarization; EU structural policy; integration; EU-Regionalpolitik; Wirtschaftsunion; Regionale Arbeitsteilung; Regionale Disparität; EU-Strukturfonds; Theorie; EU-Staaten